2019
DOI: 10.3390/ma12111756
|View full text |Cite
|
Sign up to set email alerts
|

Superplasticity of Ti-6Al-4V Titanium Alloy: Microstructure Evolution and Constitutive Modelling

Abstract: Determining a desirable strain rate-temperature range for superplasticity and elongation-to-failure are critical concerns during the prediction of superplastic forming processes in α + β titanium-based alloys. This paper studies the superplastic deformation behaviour and related microstructural evolution of conventionally processed sheets of Ti-6Al-4V alloy in a strain rate range of 10–5–10–2 s–1 and a temperature range of 750–900 °C. Thermo-Calc calculation and microstructural analysis of the as-annealed samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Many studies have focused on the superplastic properties and modeling of superplastic deformation behavior of Ti-6Al-4V alloy [6][7][8][9][10][11][12][13][14][15] and only few papers describe these phenomena in Ti-1V-4Al-3Mo alloy [16,17]. The differences in the deformation behavior of Ti-6Al-4V and Ti-1V-4Al-3Mo alloys are shown in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the superplastic properties and modeling of superplastic deformation behavior of Ti-6Al-4V alloy [6][7][8][9][10][11][12][13][14][15] and only few papers describe these phenomena in Ti-1V-4Al-3Mo alloy [16,17]. The differences in the deformation behavior of Ti-6Al-4V and Ti-1V-4Al-3Mo alloys are shown in [16].…”
Section: Introductionmentioning
confidence: 99%
“…The conditions were as follows: heating rate at 10 °C/s, residence time of 3 min, and strain rate at 5 × 10 −4 –0.05 s −1 . Three samples per condition and each specimen were deformed to a real strain of 0.6 and then immediately water-cooled to ambient temperature [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…In previous reports, it has been shown that different order polynomials can be given to well express the effect of strain on these material constants [40][41][42]. So, a seventh-order polynomial is selected for present work, as seen in Equation (8).…”
Section: Compensation Of Strainmentioning
confidence: 99%